Professora rosa-ou-azul e professora colorida: disputas entre os currículos antigênero e arco-íris na constituição de subjetividades docentes em uma escola de Educação Infantil - Paula Myrrha Ferreira Lança (2021)
This dissertation presents the results of a research that aimed to analyze the effects of the antigender offensive on the production of docent subjectivities of an Early Childhood Education public school in Belo Horizonte, here named as EMEI Acolhimento. Therefore, concepts of the post-critical curricular studies in its post-structuralist perspective were used, such as curriculum, discourse, gender, truth, subjectivity, knowledge, power, government and resistance, based on authors such as Michel Foucault and Judith Butler. The methodology was composed by interviews with five teachers that work in EMEI Acolhimento articulated with elements of the discourse analysis based on Foucault. This dissertation argues that there are two curriculums disputing the production of subjectivities of EMEI Acolhimento: the antigender and the rainbow curriculum. In the antigender curriculum there is a demand for the pink-or-blue docent subjectivity by the prescription of knowledges such as homosexuality is a mistake and gender is natural. On the other hand, in the rainbow curriculum there is a demand for the colorful docent subjectivity by the prescription that gender is a personal construction and gender is a social and historical construction. To produce these subjectivities, in both curriculums there are specific ways to conduct the teachers.